2020
DOI: 10.1111/anec.12819
|View full text |Cite
|
Sign up to set email alerts
|

T‐wave and its association with myocardial fibrosis on cardiovascular magnetic resonance examination

Abstract: Background Risk stratification in non‐ischemic myocardial disease poses a challenge. While cardiovascular magnetic resonance (CMR) is a comprehensive tool, the electrocardiogram (ECG) provides quick impactful clinical information. Studying the relationships between CMR and ECG can provide much‐needed risk stratification. We evaluated the electrocardiographic signature of myocardial fibrosis defined as presence of late gadolinium enhancement (LGE) or extracellular volume fraction (ECV) ≥29%. Methods We evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…The amplitude of the T-wave decreases with age and shifts to the right, indicating an overall longer cardiac cycle, meaning a slower heart rate. Furthermore, the T- and P-wave intervals shorten with age; moreover, the absolute magnitude of the S-peak, Q-peak, and P-wave appears to diminish with age as well, which is in accordance with [ 36 , 37 ]. It is noteworthy that the amplitude of the R-peak shows no conclusive trend with age.…”
Section: Resultssupporting
confidence: 82%
“…The amplitude of the T-wave decreases with age and shifts to the right, indicating an overall longer cardiac cycle, meaning a slower heart rate. Furthermore, the T- and P-wave intervals shorten with age; moreover, the absolute magnitude of the S-peak, Q-peak, and P-wave appears to diminish with age as well, which is in accordance with [ 36 , 37 ]. It is noteworthy that the amplitude of the R-peak shows no conclusive trend with age.…”
Section: Resultssupporting
confidence: 82%
“…Abnormalities in ventricular repolarisation, represented by the T-wave, have been associated with ventricular arrhythmic substrates such as myocardial fibrosis, and may arguably explain the relevance of these particular latent space variable for the dynamic model. 52 , 53 , 54 , 55 Related to this is the notion that there may be cardiac pathologies where beat-to-beat variations changes in the T-wave morphology are observed (e.g. due to ventricular ectopy), although it is not clear whether these variations are captured during the encoding process.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, low T wave amplitudes (#200 mV) or negative T waves were highly associated with myocardial fibrosis using cardiovascular magnetic resonance. 14 Moreover, it has also been suggested that intensive exercise can lead to acute myocardial damage. 26 Current guidelines suggest that ST depression $ 0.05 mV (0.5 mm) in anterior leads warrant further examination in athletes.…”
Section: Discussionmentioning
confidence: 99%
“…13 Other repolarization abnormalities, including low T wave amplitude (#200 mV) or negative T waves (leads II and V5) can indicate the development of myocardial fibrosis. 14 Surprisingly, literature searches found few assessments of ST abnormalities in athletes. The purpose of this study was to explore the association between resting ST segment deviations in athletes and ECG markers of cardiovascular health and typical response to aerobic training, such as relatively greater R and T wave amplitude.…”
Section: Introductionmentioning
confidence: 99%